2012
DOI: 10.1134/s0031918x1202010x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of radiation porosity formed upon irradiation in a BN-600 reactor in the fuel-element cans of cold-deformed steel EK-164 (06Kh16N20M2G2BTFR)-ID c.d.

Abstract: At present, it is the austenitic cold deformed steel EK164 (06Kh16N20M2G2BTFR) ID that is considered as a promising material for the achievement of a maximum damage (no less than 110 dpa) and max imum burnup (≥15%). In this work, we have determined the characteristics of porosity formed upon irradiation in a BN 600 reactor to the maximum damaging dose of 77 dpa in the materials of fuel element cans made of cold deformed steel EK164 ID c.d. A comparison has been made with analogous characteristics obtained ear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…Austenitic stainless steels are used as structural materials in various industries, including the nuclear power engineering [1][2][3]. In Russia, austenitic stainless steels ChS-68 (Fe-16Cr-15Ni-2Mo-Mn-Ti-V-B) and EK-164 (Fe-16Cr-19Ni-2Mo-2Mn-Nb-Ti-B) are used for the manufacture of fuel cladding shells of fast-neutron (Generation III) nuclear reactors BN-600 and BN-800 [4][5][6]. These steels have a number of attractive qualities, such as high ductility, increased heat resistance, lack of tendency to low-temperature embrittlement compared to other structural materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Austenitic stainless steels are used as structural materials in various industries, including the nuclear power engineering [1][2][3]. In Russia, austenitic stainless steels ChS-68 (Fe-16Cr-15Ni-2Mo-Mn-Ti-V-B) and EK-164 (Fe-16Cr-19Ni-2Mo-2Mn-Nb-Ti-B) are used for the manufacture of fuel cladding shells of fast-neutron (Generation III) nuclear reactors BN-600 and BN-800 [4][5][6]. These steels have a number of attractive qualities, such as high ductility, increased heat resistance, lack of tendency to low-temperature embrittlement compared to other structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…A common problem limiting the use of austenitic steels in the nuclear power industry is their radiation-stimulated swelling at high irradiation doses. The studies of radiation porosity under irradiation in the BN-600 reactor (maximum damaging dose 77 dpa) [5,6] showed that under identical irradiation conditions, steel EK-164 swells 1.5-2 times less than steel ChS-68. Some authors [5] attribute this to the increased content of Ni (19% wt.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В работах [19,20] Из табл. 2 видно, что материал оболочки ТВЭЛа № 9 имеет более высокое распухание по сравнению с ТВЭЛом № 50 при одинаковых эксплуатационных режимах.…”
unclassified
“…Заметим, что в состав стали ЭК164 включены бор и церий, не участвовавшие в процессе облучения искусственной нейронной сети. Подставляя параметры всех элементов во входной набор данных, проведем расчет при минимальном (min) и максимальном (max) содержании легирующих элементов стали ЭК164 [19]…”
unclassified